The reduction behavior of nickel in high-iron laterites under CO/CO2/N2 atmospheres - Golecruz, Renato B. (Philippine Engineering Journal)
The reduction behavior of nickel in high-iron Nonoc laterite was studied by varying the reduction temperature, reaction time and gas composition. It was observed that over a wide range of coditions,the degree of metallization increases with increasing level of any process variable, reaches some peak values, and then decreases with further increase in severity of reduction conditions. It was also noted that no more than 96.6% nickel can be metallized from the test sample. Ammoniacal leaching of pre-reduced pellets demonstrated that the Nonoc laterite is responsive to the treatment. An overall nickel recovery of about 94% is possible with this process.